Socialization of the Existence of Saccharin in Packaged Beverage Products in the Lubuk Pakam Area - Sinurat, Jhon Patar; Br Karo, Reh Malem; Yanti, Dian Anggri; Ginting, Wira Maria; Harahap, Rahmat Ali Putra; Batubara, Khairunnisa; Telova, Yurizki (JURNAL PENGMAS KESTRA (JPK), 2024)
Food quality needs to be considered, especially for the nutrition and chemical content contained therein. One of these chemicals can act as a sweetener which can enhance the taste and aroma of a product. The artificial sweetener is saccharin, which is generally added to packaged food and beverage products. However, the permitted use of saccharin in a product is around 0.005 - 0.03%. If the quantity of saccharin exceeds the threshold, it will cause health problems such as nervous diseases, hypertension, and cancer. This socialization activity aims to educate the public to be more concerned about health by carefully reading the composition of packaged beverage products before consuming them. The Community Service activity was carried out through socialization which was attended by 20 participants, namely residents around the Lubuk Pakam sub-district. The procedure for this activity includes a pre-test, provision of materials, discussion, questions and answers, and a post-test. The increase in participant knowledge is measured based on the pre-test and post-test scores of the participants. The Community Service results showed that several packaged beverage products actually contained saccharin in amounts that exceeded the threshold. In addition, this socialization also further increases awareness and presents a more careful attitude in participants in reading the composition of packaged beverage products before consuming them. Then the results showed that there was an increase in the knowledge of Community Service participants who initially dominated the category of knowledge that was not good and quite good to good and very good. The Community Service activities through this socialization have proven to be useful in increasing participants' knowledge regarding the presence of saccharin in packaged beverage products.